ChemInform Abstract: Steric vis‐a‐vis Electronic Influence of Phosphines on Biaryl Motif: Ligand Design for Coupling Reactions with Chloroarenes. Issue 22 (15th May 2015) - Saha, Debajyoti; Ghosh, Raju; Dutta, Ranjan; Mandal, Achintya Kumar; Sarkar, Amitabha
Abstract: Six new 1‐aryl‐pyrazole/pyrrole derived ligands are synthesized and evaluated in Pd‐catalyzed Suzuki—Miyaura and Hiyama coupling reactions.